2021
DOI: 10.1111/1365-2745.13644
|View full text |Cite|
|
Sign up to set email alerts
|

Lianas have more acquisitive traits than trees in a dry but not in a wet forest

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(48 citation statements)
references
References 175 publications
5
42
0
Order By: Relevance
“…In tropical semideciduous and deciduous forests, a short C gain window during the rainy season occurs due to the reduced leaf longevity (Chaturvedi et al, 2011). It has been widely observed that species from seasonal forests display high SLA and N content, whereas low leaf thickness, mostly due to the presence of drought‐avoiding species (Reich et al, 1997; Eamus, 1999; Wright et al, 2001; Givnish, 2002; Santiago et al, 2004; Powers & Tiffin, 2010; Souza et al, 2020; Medina‐Vega et al, 2021). This suite of leaf traits characterizes the “fast” resource use strategy (acquisitive leaves) in the global leaf economic spectrum (Díaz et al, 2016), which together contribute to maximizing photosynthesis when water is available (Eamus, 1999; Wright et al, 2001; Givnish, 2002; Chaturvedi et al, 2011; Souza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In tropical semideciduous and deciduous forests, a short C gain window during the rainy season occurs due to the reduced leaf longevity (Chaturvedi et al, 2011). It has been widely observed that species from seasonal forests display high SLA and N content, whereas low leaf thickness, mostly due to the presence of drought‐avoiding species (Reich et al, 1997; Eamus, 1999; Wright et al, 2001; Givnish, 2002; Santiago et al, 2004; Powers & Tiffin, 2010; Souza et al, 2020; Medina‐Vega et al, 2021). This suite of leaf traits characterizes the “fast” resource use strategy (acquisitive leaves) in the global leaf economic spectrum (Díaz et al, 2016), which together contribute to maximizing photosynthesis when water is available (Eamus, 1999; Wright et al, 2001; Givnish, 2002; Chaturvedi et al, 2011; Souza et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The wind-dispersed comose seeds, then, might have favored twining plants to disperse and occupy open and semi-arid habitats. Twining plants seem to have greater capacities for the uptake and transportation of water and are more competitive than trees in high-light, nutrientrich environments, such as the seasonally dry forests (Medina-Vega et al, 2021). Xylem adaptations to drought and cold show similar trends and possibly contributed to rapid diversification events in several lineages of angiosperms in association with the global cooling and aridification, especially after the mid-Miocene climatic optimum (Folk et al, 2020).…”
Section: Potential Key Drivers Of Apocynaceae Diversificationmentioning
confidence: 99%
“…However, investigation at the leaf scale shows that our ability to differentiate lianas and trees based on spectral properties might depend on forest type, with detectable differences in dry forests (Guzmán Q. and Sanchez-Azofeifa, 2021) but not in wet forests (Sánchez-Azofeifa et al, 2009). Similarly, liana leaves have several distinct chemical and structural properties compared to trees (Asner and Martin, 2012; Werden et al, 2018), however differences appear mediated by climatic factors, depending on temperature and being minimized in wetter forests (Asner and Martin, 2012; Medina-Vega et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%